2007
DOI: 10.1245/s10434-007-9469-6
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Netrin-1 Expression and Its Receptors in Patients with Adenocarcinoma of the Pancreas

Abstract: Expression of netrin-1 has significant impact on time to tumor relapse in adenocarcinoma of the pancreas. Netrin-1 expression is associated with worse outcome in poorly differentiated pancreatic adenocarcinomas. Risk-stratification according to the UNC5H3 receptor expression pattern shows that node positive patients (pN1) with no to little UNC5H3 expression carry a significantly worse prognosis than those with middle to strong UNC5H3 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
2
29
0
4
Order By: Relevance
“…High levels of netrin-1 were shown to correlate with adverse outcome of stage 4S and stage 4 (o1 year). A study by Link et al (2007), reporting that netrin-1 expression has significant impact on the overall survival of patients with poorly differentiated pancreas tumors, completes this description of netrin-1 upregulation in human neoplasias. Although the mechanism for autocrine production of netrin-1 remains to be determined, it could be at least in part a result of nuclear factor-kB activation, as netrin-1 is a direct target gene of this transcription factor .…”
Section: Drs Are Altered During Tumor Progressionsupporting
confidence: 55%
See 1 more Smart Citation
“…High levels of netrin-1 were shown to correlate with adverse outcome of stage 4S and stage 4 (o1 year). A study by Link et al (2007), reporting that netrin-1 expression has significant impact on the overall survival of patients with poorly differentiated pancreas tumors, completes this description of netrin-1 upregulation in human neoplasias. Although the mechanism for autocrine production of netrin-1 remains to be determined, it could be at least in part a result of nuclear factor-kB activation, as netrin-1 is a direct target gene of this transcription factor .…”
Section: Drs Are Altered During Tumor Progressionsupporting
confidence: 55%
“…Therefore, DRs can join the list of promising targets for cancer treatment. Whereas restoring the expression of an extinguished receptorcoding gene does not seem conceivable, interfering with ligand binding seems to be a more pertinent approach, further supported by recent studies reporting an overexpression of netrin-1 in various cancers (Link et al, 2007;Fitamant et al, 2008;Delloye-Bourgeois et al, 2009a, b). These studies provide an idea of what the future therapeutic molecules used in clinical studies could be; for example, a decoy receptor corresponding to the entire ectodomain of DCC receptor that would titrate the ligand, thus leading to unbound membrane receptors (Fitamant et al, 2008).…”
Section: Drs As New Therapeutic Targetsmentioning
confidence: 97%
“…This can confer to the tumor cell both a selective advantage to survive while growing in the primary site but also to migrate freely away from the 'physiological' accessibility of the ligand netrin-1, and thus to colonize other tissues and metastasize. Along this line, a cohort's study [55] shows that a high-rate netrin-1 expression significantly influences the time of relapse of patients with pancreatic adenocarcinoma and is associated with a poor prognosis. Similarly, a recent study [54 ] demonstrated a high expression of netrin-1 in metastatic neuroblastoma with poor prognosis.…”
Section: Dependence Receptors As Original Targets For Cancer Therapymentioning
confidence: 98%
“…In this sense, it was recently shown that netrin-1 is upregulated and autocrinally produced in more than 60% of metastatic breast cancer [52 ], in 47% of lung cancer [53 ], in 38% of neuroblastoma [54 ], and in a large fraction of pancreatic cancer [55]. The mechanism associated with this gain of netrin-1 is, at this stage, unclear.…”
Section: Dependence Receptors As Original Targets For Cancer Therapymentioning
confidence: 99%
“…The expression levels of Neo1 vary significantly among different cancers. For example, high expression of Neo1 was found in ESCC [13], moderate expression was displayed in pancreatic cancer [11], and low expression was revealed in breast cancer, colon cancer and glioma [7,10,12]. Our study focused on the expression of Neo1 in GC.…”
Section: Discussionmentioning
confidence: 99%